An Analysis of the Anti-Mycobacterial Activity of some Medicinal Plants: Exploring the potential of medicinal plants against mycobacterial infections (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The objective of this study is to provide a rational scientific justification for the antimycobacterialactivity of medicinal plant extracts. Mycobacterium-suppressing characteristics may befound in a variety of plants, including well-known species like Aloe vera and Ocimum sanctum as well asnotorious and swiftly spreading species like Lantana camara and Acacia senegal.